Hydrogen Peroxide Cycling in High-Temperature Acidic Geothermal Springs and Potential Implications for Oxidative Stress Response - Meslé, Margaux M.; Beam, Jacob P.; Jay, Zackary J.; Bodle, Brynna; Bogenschutz, Eric; Inskeep, William P. (Frontiers in Marine Science, 2017)
Hydrogen peroxide (H2O2), superoxide (O2•-), and hydroxyl radicals (OH•) are produced in natural waters via ultraviolet (UV) light-induced reactions between dissolved oxygen (O2) and organic carbon, and further reaction of H2O2 and Fe(II) (i.e., Fenton chemistry). The temporal and spatial dynamics of H2O2 and other dissolved compounds (Fe(II), Fe(III), H2S, O2) were measured during a diel cycle (dark/light) in surface waters of three acidic geothermal springs (Beowulf Spring, One Hundred Springs Plain, and Echinus Geyser Spring; pH = 3-3.5, T = 68-80 °C) in Norris Geyser Basin, Yellowstone National Park. In situ analyses showed that H2O2 concentrations were lowest (ca. 1 μM) in geothermal source waters containing high dissolved sulfide (and where oxygen was below detection) and increased by two-fold (ca. 2-3 μM) in oxygenated waters corresponding to Fe(III)-oxide mat formation down the water channel. Small increases in dissolved oxygen and H2O2 were observed during peak photon flux, but not consistently across all springs sampled. Iron-oxide microbial mats were sampled for molecular analysis of ROS gene expression in two primary autotrophs of acidic Fe(III)-oxide mat ecosystems: Metallosphaera yellowstonensis (Archaea) and Hydrogenobaculum sp. (Bacteria). Expression (RT-qPCR) assays of specific stress-response genes (e.g., superoxide dismutase, peroxidases) of the primary autotrophs were used to evaluate possible changes in transcription across temporal, spatial and/or seasonal samples. Data presented here documented the presence of H2O2 and general correlation with dissolved oxygen. Moreover, two dominant microbial populations expressed ROS response genes throughout the day, but showed less expression of key genes during peak sunlight. Oxidative stress response genes (especially external peroxidases) were highly-expressed in microorganisms within Fe(III)-oxide mat communities, suggesting a significant role for these proteins during survival and growth in situ.